2016
DOI: 10.1016/j.exer.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging microscopy reveals quenching of fluorescein within corneal epithelium

Abstract: Topical application of fluorescein results in background fluorescence of normal corneal epithelial cells. The fluorescence appears relatively weak and is often ignored clinically. The concentrations of fluorescein applied clinically exceed the threshold for self quenching. The possibility that exuberant topical concentrations of fluorescein result in quenching of fluorescence in tears and normal corneal epithelium is explored. Fluorescence lifetime measurements are sensitive to quenching and are less vulnerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Therefore, FLIM is well-suited for accurate measurements of quenching dynamics. 75,76 Multiple configurations or states of a fluorophore can be detected with FLIM at a single location or pixel. For example, both bound and unbound fluorophores, as well as proteins with distinct folding states, will have different molecular environments that coexist within the same pixel.…”
Section: Advantages Of Flim Over Intensity Imagingmentioning
confidence: 99%
“…Therefore, FLIM is well-suited for accurate measurements of quenching dynamics. 75,76 Multiple configurations or states of a fluorophore can be detected with FLIM at a single location or pixel. For example, both bound and unbound fluorophores, as well as proteins with distinct folding states, will have different molecular environments that coexist within the same pixel.…”
Section: Advantages Of Flim Over Intensity Imagingmentioning
confidence: 99%
“…Significant reductions (P<0.05) in fluorescence intensity of all tested nanoparticles and sodium fluorescein was evident after 2 hours of incubation on the skin surface and prior to tape stripping. The fluorescence intensity reduced to 12, 52, 7 and 10% for sodium fluorescein, TSNPs, PEGylated 750 Da and PEGylated 5000 Da TSNPs respectively which could be attributed to quenching of fluorescein (Glasgow, 2016;Song et al, 1995) and penetration into the follicles. Teichmann et al reported recovery of 95% of sodium fluorescein dye from stratum corneum and 5% from follicular infundibula after differential stripping (Teichmann et al, 2005).…”
Section: Tape Stripping Studymentioning
confidence: 93%
“…The model trajectory is only significantly close to point A, and at this point t = 1.43 Q ns. In the context of Glasgow et al [23], this extent of quenching would correspond to a local concentration of fluorescein of 18 mM.…”
Section: Compartmentalised Modelmentioning
confidence: 96%
“…Therefore, the intracellular protein concentration is ~1.66 mM. Even if the labelling efficiency was 100% and all proteins had been tagged by one fluorophore, 1.66 mM of fluorescein would only be able to quench the average lifetime down to ~3.8 ns via random collisions [23]. This is insufficient to explain the 2.64 ns average lifetime obtained on day 1.…”
Section: Random Modelmentioning
confidence: 97%